PENGEMBANGAN EVALUASI PENDIDIKAN AGAMA ISLAM PADA PERGURUAN TINGGI MELALUI PROGRAM PEMBINAAN KEAGAMAAN MAHASISWA - Akmal Syarifudin Zaidan; Ubaidillah Fadli Achmad; Ihda Maulidya Khothrun Nabila; Ririn Mu'tamiroh, Siti; Ulfa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an evaluation model for Islamic Religious Education (IRE) in higher education that not only focuses on cognitive achievement but also encompasses students’ spiritual, moral, and socio-religious development. The research employed a qualitative approach using a library research method by analyzing various scholarly sources related to educational evaluation, Islamic Religious Education, and religious development programs for university students. The findings reveal that the current evaluation system of IRE in higher education is predominantly centered on academic assessment through examinations and coursework, which has not adequately reflected the comprehensive learning outcomes of students. Therefore, this study proposes an evaluation model based on students’ religious development programs, including the enhancement of Qur’anic reading and comprehension skills, spiritual and worship development, character and moral development, as well as socio-religious engagement and community service activities. The proposed model is expected to provide a more holistic evaluation system for measuring the effectiveness of Islamic Religious Education and to support the development of knowledgeable, morally upright, spiritually grounded, and socially responsible graduates